2019
DOI: 10.1038/s41560-019-0412-4
|View full text |Cite|
|
Sign up to set email alerts
|

Estimation of losses in solar energy production from air pollution in China since 1960 using surface radiation data

Abstract: China is the largest worldwide consumer of solar photovoltaic (PV) electricity, with 130 GW of installed capacity as of 2017. China's PV capacity is expected to reach at least 400 GW by 2030, to provide 10% of its primary energy. However, anthropogenic aerosol emissions and changes in cloud cover affect solar radiation in China. Here, we use observational radiation data from 119 stations across China to show that the PV potential decreased on average by 11-15% between 1960 and 2015. The relationship between ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(56 citation statements)
references
References 40 publications
0
56
0
Order By: Relevance
“…G1.0/250 < G0.5/250 < Ti250). On the contrary, when the specimens were thermally treated at 450 °C / 2h, IPA oxidation had this trend: G1.0/450 > G0.5/450 > Ti450, even though the rise in photocatalytic activity was tiny (18,15, and 14 ppm.h -1 , respectively).…”
Section: Specimens Thermally Treated At 450 °C / 2h Have In General Amentioning
confidence: 91%
See 1 more Smart Citation
“…G1.0/250 < G0.5/250 < Ti250). On the contrary, when the specimens were thermally treated at 450 °C / 2h, IPA oxidation had this trend: G1.0/450 > G0.5/450 > Ti450, even though the rise in photocatalytic activity was tiny (18,15, and 14 ppm.h -1 , respectively).…”
Section: Specimens Thermally Treated At 450 °C / 2h Have In General Amentioning
confidence: 91%
“…Moreover, ground-level ozone (O 3 ) is formed by photochemical reactions between sunlight and NO x and VOCs [17], this again having an adverse impact on human health and climate. Additionally, those anthropogenic aerosols emissions are even able to (partly) obscure the sun, as it has been shown that up to 15% of photovoltaic electricity has been "lost" in China between 1960 and 2015 because of the increased air pollution [18]. However, in 2014, China introduced an ultra-low emissions standards policy to limit the emissions of those anthropogenic aerosols [19].…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of particulate matter reduce solar electricity generation due to the changed solar irradiance. The emission of aerosols can attenuate solar radiation by scattering and absorbing sunlight before it reaches the solar panel 21 , and thus reduces photovoltaic (PV) performance 22,23 . Large particles in particulate matter can also generate dust on top of solar panels.…”
mentioning
confidence: 99%
“…In areas with severe air pollution such as China, the potential of solar PV generation decreased on average by 11-15% between 1960 and 2015 (ref. 22 ); the decrease of point-of-array irradiance can even reach 35% in the most polluted areas 23 . Such interaction adds another dimension to the complexity of assessing pollution externalities.…”
mentioning
confidence: 99%
“…Global high-quality SW/PAR data at sub-daily scales are highly desired for investigating the diurnal variabilities of solarinduced fluorescence, photosynthesis (Damm et al, 2010) and evapotranspiration (Van Heerwaarden et al, 2010), and for solar energy utilization (Sweerts et al, 2019). However, accurately quantifying global SW/PAR is challenging based on current polarorbiting or/and geostationary satellites/sensors, because: 1) sun-synchronous polar-orbiting satellites generally have high spatial 55 resolution but cannot capture the sub-daily variations of SW/PAR owing to low revisiting frequency; 2) geostationary satellites usually have high temporal resolution but limited geographical coverage (i.e.…”
mentioning
confidence: 99%